An eighteenth century travelling theodolite - Isabel Malaquias (História, Ciências, Saúde: Manguinhos)
Abstract An old topographic compass displayed in a showroom of the Museu de Astronomia e Ciências Afins (MAST), in Rio de Janeiro, Brazil, took our curiosity namely because of its resemblance to a theodolite, described by J.H. de Magellan. Not many things were known about its previous history. From the different documents studied, and the characteristics of this singular theodolite, it must have belonged to the collections of instruments acquired for the Brazilian border demarcations undertaken after the Santo Ildefonso Treaty, agreed to by the Portuguese and Spanish courts in 1777. Several instruments were bought in London, and supervised and chosen by Magellan, the Portuguese instruments expert. We present arguments in favour of this conclusion.